2008
DOI: 10.2147/dddt.s3732
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Bis-Maltolato-OxoVanadium(IV): Conversion of inactive trans- to bioactive cis-BMOV for possible binding to target PTP-1B

Abstract: Abstract:The postulated transition of Bis-Maltolato-OxoVanadium(IV) (BMOV) from its inactive trans-into its cis-aquo-BMOV isomeric form in solution was simulated by means of computational molecular modeling. The rotational barrier was calculated with DFT -B3LYP under a stepwise optimization protocol with STO-3G, 3-21G, 3-21G*, and 6-31G ab initio basis sets. Our computed results are consistent with reports on the putative molecular mechanism of BMOV triggering the insulin-like cellular response (insulin mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…35 The mass spectral data shows close agreement with the supposed molecular structure of the complex (4).…”
Section: Mass Spectrometry Insightssupporting
confidence: 72%
See 1 more Smart Citation
“…35 The mass spectral data shows close agreement with the supposed molecular structure of the complex (4).…”
Section: Mass Spectrometry Insightssupporting
confidence: 72%
“…Density-functional theory (DFT) is a powerful method for predicting the geometry of vanadium compounds including large molecules [31][32][33][34][35][36][37]. The application of theoretical force constants to attain Cartesian representation is useful for the assumption of molecular symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, due to the reported identification of a biomolecular target we could devise a so-called de novo design procedure. In a previous work, 35 we demonstrated that vanadium compounds stated in the literature as the most active antidiabetics are also potential PTP1B inhibitors. 35 Particularly, in the case of bis(maltolate) oxo-vanadium(IV) (BMOV) and ammonium bis(picolinate) oxo-vanadium(V), we determined the active conformations during simulated docking into the target enzyme (PTP1B).…”
Section: Introductionmentioning
confidence: 75%
“…31 Recently, literature evidence appears in support of the hypothesis that active vanadium compounds may have intrinsic affinity to the PTP1B catalytic site. [32][33][34][35] The insulin-like properties of vanadium have been demonstrated in a conclusive way based on in vitro experiments, 36 in vivo assays in rats 37,38 or mice, 39 as well as in patients with diabetes. 40 It is noteworthy to state that as yet all clinical studies have been carried out successfully using inorganic salts of vanadium, albeit it is beyond doubt that the true potential lies in the use of organic vanadium complexes, judging from the higher activity and the lower toxicity rates.…”
Section: Introductionmentioning
confidence: 99%
“…Density-functional theory (DFT) is a powerful method for predicting the geometry of vanadium compounds [31][32][33][34][35][36] including large molecules [37]. The application of theoretical force constants to attain Cartesian representation is useful for the assumption of molecular symmetry.…”
Section: Introductionmentioning
confidence: 99%